The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1007/bf00880778
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of “shows” and “no‐shows” to a crisis center

Abstract: The relationship between measures of worker effectiveness in a therapeutic telephone intervention and whether a caller shows for a scheduled appointment can be used to assess the variables that contribute to "successful" telephone counseling. This study replicated the findings of a previous investigation in showing that the motivation of a caller in response to the question of a referral was positively correlated with "showing" for the appointment. Futher, the identification of a specific problem related negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1977
1977
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…(1973), Slaikeu, Tulkin, & Speer, (1975), and Walfish, Tapp, Tulkin, Slaikeu, & Russel (1975) have been able to show a relationship between certain client/counselor interactions and the probability that the client will actually keep a scheduled appointment for face-to-face counseling. It is likely that variables such as follow-up timing, frequency, and/or target (OP or 00) are important in facilitating the beginning of counseling.…”
Section: Resultsmentioning
confidence: 99%
“…(1973), Slaikeu, Tulkin, & Speer, (1975), and Walfish, Tapp, Tulkin, Slaikeu, & Russel (1975) have been able to show a relationship between certain client/counselor interactions and the probability that the client will actually keep a scheduled appointment for face-to-face counseling. It is likely that variables such as follow-up timing, frequency, and/or target (OP or 00) are important in facilitating the beginning of counseling.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding TE, no evidence has been presented tying this variable to independent measures of outcome. The total TE score has been found to be uncorrelated with outcome as measured by client self-report of satisfaction with the call when recontacted within 24 hours (Wilson et al,Note 4), and with outcome evaluated in terms of whether the caller subsequently appeared for a scheduled appointment (Tapp, Slaikeu, & Tulkin, 1974;Walfish, Tapp, Tulkin, Slaikeu, & Russell, 1975).…”
Section: Non-suicide-related Measuresmentioning
confidence: 99%
“…The effectiveness of telephone interventions with medical patients other than those with cancer is wellestablished (Hornblow 1986). A number of studies have demonstrated that telephone support confers significant benefits, including enhanced compliance in health care (Walfish et al 1975;Lando et al 1992); resource savings (Weinberger et al 1993); and improvements in both family (Johnson & Frank 1995) and patient well-being (Hornblow & Sloane 1980;Evans et al 1984Evans et al , 1985Shepard 1987;Hallam 1989;Preston et al 1992;Cherry & Rubinstein 1994). Since the patients who have been the subjects of such studies suffer from many of the same kinds of psycho-social problems as cancer patients, such as depression, anxiety, loneliness, and social concerns (e.g.…”
Section: Introductionmentioning
confidence: 99%